2018
DOI: 10.1002/jcop.22150
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in linkage to mental health care program in the Rockaways after Hurricane Sandy

Abstract: The Rockaways area of New York City was especially devastated by Hurricane Sandy. This study examined participant characteristics associated with acceptance of a linkage to and attendance at appointments for mental health difficulties (MHD). Participants (N = 1,011) completed questionnaires to assess mental health symptoms. Participants who met screening criteria (n = 442) were offered linkage to care. Individuals who had a higher mental health symptom burden (MHSB; i.e., those who screened in on more than one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…PR, a foundation-funded study, used the same survey as LIGHT but included only residents who lived in the Rockaways (Queens, New York) when Hurricane Sandy hit; participants were recruited from 5 June 2014 to 9 August 2016. Further details about study design can be found in Bevilacqua et al 28 Of note, both studies used convenience sampling in that interested potential participants approached the research booth at various places, like street fairs, libraries and supermarkets. Exclusion criteria were not speaking English or Spanish, having cognitive impairments that would prevent informed consent, being under 18 years old, or not living in Long Island or New York City during Hurricane Sandy.…”
Section: Light/prmentioning
confidence: 99%
“…PR, a foundation-funded study, used the same survey as LIGHT but included only residents who lived in the Rockaways (Queens, New York) when Hurricane Sandy hit; participants were recruited from 5 June 2014 to 9 August 2016. Further details about study design can be found in Bevilacqua et al 28 Of note, both studies used convenience sampling in that interested potential participants approached the research booth at various places, like street fairs, libraries and supermarkets. Exclusion criteria were not speaking English or Spanish, having cognitive impairments that would prevent informed consent, being under 18 years old, or not living in Long Island or New York City during Hurricane Sandy.…”
Section: Light/prmentioning
confidence: 99%